Sociodemographic determinants of multimorbidity in Brazilian adults and older adults: a cross-sectional study - Christofoletti, Marina; Duca, Giovani Firpo Del; Benedetti, Tânia Rosane Bertoldo; Malta, Deborah Carvalho (São Paulo Medical Journal, 2022)
BACKGROUND: Multimorbidity due to non-communicable chronic diseases (NCDs) constitutes a significant challenge for healthcare systems. To attenuate its impacts, it is essential to identify the sociodemographic determinants of this condition, which can discriminate against population segments that are more exposed. OBJECTIVE: To identify associations between multimorbidity conditions and sociodemographic indicators among Brazilian adults and older adults. DESIGN AND SETTING: Cross-sectional telephone-based survey in 26 Brazilian state capitals and the federal district. METHODS: The Vigitel 2013 survey was used, with data collected via a questionnaire. The outcome was multimorbidity (2, 3 or 4 NCDs), and the exposures were sociodemographic indicators (age, sex, skin color, marital status and education). The analysis consisted of multinomial logistic regression (odds ratio), stratified by age. RESULTS: Among adults, multimorbidity comprising two, three or four diseases was associated with advancing age (P < 0.001); two and three diseases, with having a partner (P = 0.004 and P < 0.001, respectively); and two, three or four diseases, with lower education (P < 0.001). Among older adults, two, three or four diseases were associated with female sex (P < 0.001); three diseases, with living with a partner (P = 0.018); two diseases, with black skin color (P = 0.016); and two or three diseases, with lower education (P < 0.001). CONCLUSIONS: To control and prevent multimorbidity, strategies for individuals with existing chronic diseases, with partners and with lower education levels are needed. Particularly for adults, advancing age should be considered; and for older adults, being a woman and having black skin color.